"A More Powerful Effect upon the Body": Early Mormonism's Theory of Racial Redemption and American Religious Theories of Race. Issue 3 (8th November 2018) - Stuart, Joseph R.
Abstract : This paper examines Joseph Smith's construction of a racialized theology, which drew upon conceptions of Abrahamic lineage and the possibility of "racial redemption" for peoples of African descent through conversion to Mormonism. This ran against the grain of his Protestant and Catholic contemporaries' religious understandings of race. He expanded upon earlier iterations of his ideas with the introduction of new rituals and liturgy related to LDS temples. Smith's wife may have invited a person of African descent to participate in this new liturgy before his murder in June 1844. The views he expressed about peoples of African descent before his death are inchoate, although high-ranking Mormons related to Smith seemed to have agreed with the possibility of racial redemption. After Smith's death, Brigham Young and other Mormon leaders framed the LDS temple and priesthood restriction in terms of Smith's liturgy rather than any of Smith's varied teachings on race. This paper also argues that Mormonism's racial restriction arose from its roots in the sealing ritual rather than ecclesiological power structures. Mormonism's racial doctrine has often been described as a "priesthood ban, " referring to ecclesiastical authority. However, this discounts the religious contexts in which it arose and excludes the experiences of women and children, who were not allowed to participate in the endowment or sealing ordinances. This paper places Mormonism's temple liturgy at the front and center of the LDS Church's priesthood and temple restriction.